Economic and Technical Feasibility of Metering and Sub-metering Systems for Heat Accounting - Celenza, Luca; Dell'Isola, Marco; Ficco, Giorgio; Greco, Marco; Grimaldi, Michele (International Journal of Energy Economics and Policy, 2016)
The Energy Efficiency Directive 2012/27/EU (EED) requires that final users in multi-apartment buildings supplied by common central heating source should be provided by 31 December 2016 with accounting systems, as long as technical feasibility and reasonable costs in relation to the potential energy savings can be demonstrated. Such systems would reflect users actual thermal energy consumption. The typical configuration of Italian multi-apartment buildings implies quite expensive installation costs and sometimes even prevents the installation for technical reasons. Coherently with EED, in such cases alternative cost-efficient methods for heat accounting should be adopted, such as indirect methods. This study assesses the economic and technical feasibility of the most common heat accounting systems. In this paper, after a brief analysis of the different approaches adopted in EU member states, the authors present a cost/benefit analysis that considers the main capital and running costs of individual heat accounting systems with respect to the potential energy savings achievable. Keywords: energy efficiency, heat accounting, cost efficiency. JEL Classifications: O31, O33